Double Standards in Human Rights Interpretation (Comparison of American and Asian Practices) - Sanjaya, Aldo Dicky; Faisal, Mokhammad Kahvi (Faculty of Law, Universitas Negeri Semarang, 2023)
This paper explores the phenomenon of double standards in the interpretation and application of human rights principles, with a comparative analysis between American and Asian practices. Through an examination of key case studies and legal frameworks, it delves into the disparities and inconsistencies that arise in the treatment of human rights issues across these regions. The study elucidates how cultural, political, and historical factors shape differing perspectives on human rights, leading to divergent approaches in addressing violations and advocating for protections. Drawing upon empirical evidence and scholarly discourse, the paper highlights instances where double standards manifest in human rights discourse, such as the selective condemnation of human rights abuses based on geopolitical interests or cultural biases. It examines how interpretations of rights, such as freedom of expression and assembly, vary between the American and Asian contexts, often resulting in contrasting legal norms and enforcement mechanisms. Furthermore, the paper analyzes the impact of these double standards on marginalized communities and the effectiveness of international human rights mechanisms in promoting accountability and justice. In conclusion, the paper underscores the importance of recognizing and addressing double standards in human rights interpretation to ensure equitable treatment and protection for all individuals regardless of nationality or cultural background. It calls for greater transparency, consistency, and collaboration in upholding universal human rights standards, thereby fostering a more just and inclusive global society.